Investigations of plasma response associated with resonant magnetic perturbation fields using perturbation method in KSTAR H-mode plasmas. (1st June 2022) - Xiao, W.W.; Evans, T.E.; Tynan, G.R.; Orlov, D.M.; Yoon, S.W.; Ko, W.H.; Kim, M.W.; Jeon, Y.M.; Nam, Y.U.; Oh, Y.K.; KSTAR Team
Abstract: The plasma response associated with the resonant magnetic perturbation (RMP) field was investigated using the small edge perturbations induced by a modulated supersonic molecular beam injection (SMBI) in KSTAR. The modulated SMBI provides a time-varying perturbation of the plasma density source in the region just inside the last closed flux surface and a modulated flow damping rate. Radial propagation of the toroidal rotation perturbation induced by SMBI from the q = 3 surface to the q = 2 surface was observed. Theoretical analysis using the general perturbed equilibrium code of the RMP intensity profiles of the RMP field is consistent with the phase profile of the toroidal rotation perturbation.